Mechanical properties of trays based on starch of native plant species and fiber of agroindustrial wastes - Espina, Miguel (2016)
The aim of this study was to evaluate the effect of natural fibers derived from agro-industrial waste in density, weight and mechanical properties of the termoprensadas foams made of starch native species, such as sweet potatoes, oca and arracacha. The thermoforming process was carried out at a temperature of 145 ° C and a pressure of 60 bar. The baking time was 10-15 min depending on water content in the mixture. The trays were characterized by their density, weight, impact test, deflection tests, colorimetry, hardness, and fracturability values. The trays prepared by thermopressure based on sweet potato starch-bagasse fiber from sugar cane at 15%, and arracacha starch -peladilla asparagus fiber at 30% had higher values in flexural strength versus those made with other types of starches and fibers, including blank tests. Generally, the hardness of the trays is favored with increasing fiber, however fracturability decreases or does not improve the integrity of the polymeric matrix. The results shown in this study allow the preparation of biodegradable trays for various industrial applications.